Resisting “Liberal Values”: The Intersection of Gender, Religion, and Sexuality in Ukrainian Heteroactivism - Shevtsova, Maryna (ACME, 2023)
During the previous decade (2012–2021), in Ukraine, political pressure from the European Union combined with the efforts of the local civil society resulted in the adoption of legislation to prevent and eliminate discrimination, protect women from domestic violence, and promote LGBT people’s rights. Nevertheless, these changes were met by the opposition from various conservative and religious groups that have, over time, become more sophisticated in their resistance strategies. The present article applies the concept of heteroactivism to examine the role of women within such groups in Ukraine. It argues that Ukrainian heteroactivism is a product of the “clash of values” largely influenced by the geopolitical position of Ukraine and its historical and cultural context. Studying the cases of the Sisterhood of St. Olga, the Association of Sexologists and Sexual Therapists of Ukraine (ASSU), and several prominent scholarly figures, the article identifies the mobilization frames these activists use, specifically, Women as Wives and Mothers, Protection of Family and Minors, and Religion (heteroactivism as martyrdom). This study shows that in attempts to influence national policymaking, Ukrainian women heteroactivists set rigid standards of “proper” Ukrainian femininity and the role of women (that of a mother and wife staying outside of politics) within a “proper” Ukrainian family, which must be heterosexual, Christian, and monogamous.